Sie sind auf Seite 1von 3

An Interesting Summation

Cristian Bicheru

1/9/2019

Problem:

Find

X cos(n)
.
n=1
n

Solution:

Note: ∞
1
Z
e−nt dt = .
0 n

Thus
∞ ∞  Z ∞ 
X cos(n) X
= cos(n) e−nt dt
n=1
n n=1 0

∞ Z
X ∞ 
= cos(n)e−nt dt
n=1 0

∞ Z ∞ 
1X
= (eni + e−ni ) e−nt dt
2 n=1 0
Z "∞ #
1 ∞ X ni −ni −nt
= (e + e ) e dt
2 0 n=1
Z "∞ ∞
#
1 ∞ X eni X e−ni
= + dt
2 0 n=1
ent n=1 ent
Z " ei e−i
#
1 ∞ et et
= i + dt
2 0 1 − eet 1 − eet
−i

1 ∞ ei
Z  
e−i
= + dt
2 0 et − ei et − e−i
ei
Z ∞ Z ∞ 
1 e−i
= dt + dt
2 0 et − ei 0 et − e−i

Now to evaluate
ei
Z
dt.
et − ei

1
We can take the constant term ei out of the integral, and perform a u substitution on the denominator:
1
Z
i
=e dt
et − ei

u = et − ei du = et dt
1
Z
= ei du.
u(u + ei )
Using partial fraction decomposition we get:
1 1
Z Z
= du − du
u u + ei

= log |u| − log |u + ei | + c



u
= log +c
u + ei
t
e − ei

= log + c.
et

The second integral has a very similar solution, the result is:
t
e − e−i
log + c.
et
Plugging this back in we get:
−i ∞
 t
e − ei
t 
1 + log e − e

= log
2 et et
0
 2t t i
 ∞
1 e − e (e + e ) + 1
−i
= log
2 e2t
0
e2t − et (2 cos(1)) + 1 ∞
 
1
= log .
2 e2t
0
Let 2t
e − et (2 cos(1)) + 1

f (t) = log
.
e2t
We need to find f (0) and
lim f (t).
t→∞

First, f (0):
1 − 1(2 cos(1)) + 1
f (0) = log

1
= log |2 − 2 cos(1)| .

Next the limit: 2t


e − et (2 cos(1)) + 1

lim f (t) = lim log

t→∞ t→∞ e2t

1 1
= lim log 1 − t (2 cos(1) + 2t )
t→∞ e e
= log |1|
= 0.

Thus the sum is equal to:


1
= [0 − log |2 − 2 cos(1)| ]
2

2
1
= − log |2 − 2 cos(1)|
2
 
1 1
= log csc
2 2
≈ 0.04202.